Modeling and control of a three-phase power supply - Contreras, José; Barbi, Ivo (Rev. Téc. Fac. Ing. Univ. Zulia)
This article presents the modeling and control of a three-phase high power factor PWM-ZVS power supply with a single power stage. A model of small signals of the converter is developed by using the PWM switch technique. The transfer function which describes the dynamic behavior of the converter is obtained from the model. A complete scheme to calculate the parameters and coefficients of the developed model, as well as the controlling systems are presented. Simulations confirm the proposed theoretic strategy.